An in-depth study of thermal effects in reset transitions in HfO2 based RRAMs. (September 2015) - Villena, M.A.; González, M.B.; Roldán, J.B.; Campabadal, F.; Jiménez-Molinos, F.; Gómez-Campos, F.M.; Suñé, J.
Highlights: Reset processes in RRAMs have been studied for different external temperatures. RRAMs I – V curves have been simulated and measured to study their temperature behavior. Models of RRAM filament metallic species diffusion have been developed. Abstract: Reset transitions in HfO2 based RRAMs operated at different temperatures have been studied. Ni/HfO2 /Si-n + devices were fabricated and measured at temperatures ranging from 233 K to 473 K to characterize their reset features. In addition, a simulator including several coupled conductive filaments, series resistance and quantum effects was employed to analyze the same devices. The experimental results were correctly reproduced. It was found that the reset voltage and current show slight temperature dependence. To explain this fact, the roles of the out-diffusion of metallic species from the conductive filament and its conductance temperature dependence have been studied by simulation. The different conductive filament resistance components are also analyzed in the temperature range employed in our study. Finally, the thermal change in the energy barrier linked to quantum effects in the transport properties in the filament is modeled.